2009
DOI: 10.1001/archneurol.2009.1
|View full text |Cite
|
Sign up to set email alerts
|

Defining Survival as an Outcome Measure in Amyotrophic Lateral Sclerosis

Abstract: To examine how respiratory interventions affect survival as an outcome measure and to define survival rate for trials in amyotrophic lateral sclerosis. Design and Setting: We reviewed the data of 3 phase 3 clinical trials and examined differences in times to death, tracheostomy, and permanent assisted ventilation. We assessed the outcomes with 2 and Fisher exact tests for categorical variables and unpaired, 2-tailed t tests for continuous variables. We used Kaplan-Meier methods to estimate the differences in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 17 publications
0
31
0
1
Order By: Relevance
“…In addition to weakness of peripheral muscles, respiratory muscle weakness develops during the course of the disease, leading to reduced alveolar ventilation and respiratory failure, which is the main cause of death in ALS. 1,2 A randomized controlled trial showed improvement in survival and quality of life (QoL) in ALS patients treated with noninvasive ventilation (NIV). 3 Although survival in the subgroup of patients with severe bulbar impairment did not improve, small improvements in QoL were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to weakness of peripheral muscles, respiratory muscle weakness develops during the course of the disease, leading to reduced alveolar ventilation and respiratory failure, which is the main cause of death in ALS. 1,2 A randomized controlled trial showed improvement in survival and quality of life (QoL) in ALS patients treated with noninvasive ventilation (NIV). 3 Although survival in the subgroup of patients with severe bulbar impairment did not improve, small improvements in QoL were observed.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with findings from a pooled analysis (in 2,477 patients with ALS) reporting that relatively high VC values may be observed close to a clinical meaningful event (e.g., tracheostomy) Table E2. (25). In that study, VC measurements were available for 50 patients with ALS requiring tracheostomy within 30 days of the need for tracheostomy, and were 50% or more of the predicted value in 11 patients, 60% or more of the predicted value in seven patients, and 70% or more of the predicted value in five patients.…”
Section: Significance Of the Findingsmentioning
confidence: 99%
“…Non-invasive ventilation unfortunately will not prevent a fatal event at final stages of disease as death by respiratory failure [33]. However, respect the limits of tolerance of patients as well as validate their complaints, recognize symptoms of discomfort related to mask-such as face/nose pain, nasal congestion, aerophagia and sleep disruption can influence a proper compliance [34].…”
Section: Discussionmentioning
confidence: 99%